2013
DOI: 10.1130/ges00833.1
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of gravity and magnetic data and development of two-dimensional cross-sectional models for the Border Ranges fault system, south-central Alaska

Abstract: Extensive Quaternary glacial cover and a lack of dense geophysical data within the Cook Inlet basin (CIB) of south-central Alaska make locating and determining the geometry of the Border Ranges fault system (BRFS), a major feature of the AlaskaAleutian forearc region, diffi cult. We use recently collected gravity data, available aeromagnetic data, and other geophysical information as constraints to develop plausible two-dimensional cross-section models that better image the BRFS and related geologic structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 49 publications
6
36
0
Order By: Relevance
“…The subduction of these sediments may have caused duplex stacking and regional antiform development beneath the coastal mountains, which drives the long-term rock uplift and rapid exhumation observed there. New gravity and published magnetic data and 2.5-D cross-sectional models across the western Chugach Mountains are consistent with low-density sediments being subducted beneath the accretionary complex since the Neogene (Mankhemthong et al, 2013). We speculate that for the last ~5 m.y., coincident with deposition of the Yakataga Formation and foreland basin development in the Saint Elias orogen (Plafker, 1987;Lagoe et al, 1993), fl atslab subduction may have carried the sediments northwest with the Yakutat microplate, where they were focused into the region beneath the Chugach core and underplated.…”
Section: Drivers Of Exhumation In the Last 5 Million Years: Tectonicssupporting
confidence: 65%
See 1 more Smart Citation
“…The subduction of these sediments may have caused duplex stacking and regional antiform development beneath the coastal mountains, which drives the long-term rock uplift and rapid exhumation observed there. New gravity and published magnetic data and 2.5-D cross-sectional models across the western Chugach Mountains are consistent with low-density sediments being subducted beneath the accretionary complex since the Neogene (Mankhemthong et al, 2013). We speculate that for the last ~5 m.y., coincident with deposition of the Yakataga Formation and foreland basin development in the Saint Elias orogen (Plafker, 1987;Lagoe et al, 1993), fl atslab subduction may have carried the sediments northwest with the Yakutat microplate, where they were focused into the region beneath the Chugach core and underplated.…”
Section: Drivers Of Exhumation In the Last 5 Million Years: Tectonicssupporting
confidence: 65%
“…Refl ectors from deep seismic-refl ection profi les from just southwest of the Kenai Peninsula are interpreted to represent Eocene underplating southeast of the Border Ranges fault system (Moore et al, 1991;Ye et al, 1997). New gravity and published magnetic data and 2.5-dimensional cross-sectional models across the Cook Inlet basin and Border Ranges fault system are consistent with low-density sediments being subducted beneath the accretionary complex (Mankhemthong et al, 2013). Bulk uplift is also consistent with the thermal-mechanical models of Koons et al (2010), which show increased vertical velocities in their convergent sub-boundary area above the subducting Yakutat microplate and adjacent to the Chugach core region.…”
Section: Mechanisms Of Rock Uplift In the Western Chugach Mountainsmentioning
confidence: 53%
“…The Benowitz et al (2011) paper on the exhumational history along the Denali fault and the Trop et al (2012) study of the Wrangell Mountains volcanic and sedimentary basins contribute important new regional information on the general consequences of the fl at-slab subduction of the Yakutat microplate beneath southern Alaska. Mankhemthong et al (2013) provide new data on the history and geometry of the Cook Inlet Basin, immediately west of the St. Elias orogen, that give information on the western fringe of the orogenic system. Thus, these studies, together with the STEEP studies in the volume, provide an important new regional data set for synthesis of this important orogenic system.…”
Section: Themed Issue Contentsmentioning
confidence: 98%
“…Possible reasons for this increased exhumation are discussed, and include a tectonic forcing and a climate driven signal due to the beginning of glacial erosion. Mankhemthong et al (2013) seek to locate and determine the geometry of the Border Ranges fault system, a major feature of the Alaska-Aleutian forearc region, using gravity, aeromagnetic, and other geophysical data in the Cook Inlet Basin region. They present 2.5D cross sections showing 6-10-km-thick sedimentary cover over the Peninsular terrane, the lithospheric mantle of which is serpentinized at depths of 14-34 km.…”
Section: Themed Issue Contentsmentioning
confidence: 99%
“…Pavlis et al (2012) suggested that sediments originally shed from the Saint Elias orogen 2-3 Ma in response to cooling climate and glacial erosion caused duplex stacking and underplating under the Yakataga segment farther to the southeast. Mankhemthong et al (2013) used gravity and magnetic data from the Chugach Mountains north of Prince William Sound to suggest that sediments shed from the Saint Elias Mountains were carried along and underplated above the Yakutat microplate. Thus, the increased volume of subducting sediments starting ca.…”
Section: Causes Of Rock Uplift and Exhumationmentioning
confidence: 99%